Antibacterial Activities of Pseudomonas orientalis APD 16 Isolate Sponge-Associated Aplysina sp. from Enggano Island Against Escherichia coli and Staphylococcus aureus - Wibowo, Risky Hadi (Operations Research: International Conference Series, 2020)
Sponge is one of the invertebrates from the Porifera phylum. Sponge bodies have structural complexity with different cell layers. The sponge has many pores (ostium) on the surface of their body as a filter feeder. Sponge is recognized as organisms that have the potential because they can produce metabolites. Secondary metabolites produced by sponges are the result of the association of sponges with bacteria. The sponge used in this study is the Aplysina sp. sponge collected from Enggano island, Bengkulu Province. Aplysina sp. sponge is known to contain metabolites with antibacterial, antifungal and cytotoxic activity on cancer cells. This study aims to identify of potential isolate associated with Aplysina sp. sponge collected from Enggano island. Isolation of bacteria from Aplysina sp. sponge using Sea Water Complete (SWC) media. The isolate was screened by antagonistic test, morphological characters, Gram-staining, biochemical test and molecular identification. Based on the antagonistic test, APD 16 isolate could inhibit Escherichia coli and Staphylococcus aureus in Vitro. APD 16 isolate was identified molecularly using of 16S rRNAgenes analysis and it genetically close with Pseudomonas orientalis.